Muslim Minorities in Western Societies: The Medieval Scene - Al-Rahim, Muddathir ’Abd (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Muslim Minorities in Western Societies: The Medieval Scene